The Role of the International Court of Justice in Resolving Disputes Between Sovereign States - Marisa, Wiwin; Meliana, Sherly; Praditya, Habib (Media Hukum Indonesia (MHI), 2025)
This study explores the role of the International Court of Justice in resolving disputes between countries using a normative juridical approach. The International Court of Justice, as the principal organ of the United Nations (UN), functions to peacefully resolve international disputes. The dispute resolution process includes case submissions, written and oral examinations, and preliminary objections. The UN's support in the form of procedural recommendations also contributes to the effectiveness of dispute resolution. The International Court of Justice has jurisdiction over disputes involving civil law, criminal law, diplomatic relations, and asylum, as long as they fall within the scope of international law. This court also provides advisory opinions to UN organs such as the General Assembly and the Security Council. The prohibition of the use of force and the emphasis on peaceful dispute resolution are imperative norms in international relations. This study emphasizes the importance of applying international legal principles to achieve global peace and avoid armed conflicts that could threaten global stability. The International Court of Justice plays a crucial role in promoting international harmony through binding decisions and the enforcement of international legal principles. Through the analysis of various dispute cases, this study demonstrates that the resolutions provided by the International Court of Justice not only help maintain peace but also strengthen the international legal order. Thus, the International Court of Justice serves as an essential instrument in achieving the UN's primary goal of creating sustainable global peace and security.